2013
DOI: 10.5598/imafungus.2013.04.02.04
|View full text |Cite
|
Sign up to set email alerts
|

Septoria-like pathogens causing leaf and fruit spot of pistachio

Abstract: Several species of Septoria are associated with leaf and fruit spot of pistachio (Pistacia vera), though their identity has always been confused, making identification problematic. The present study elucidates the taxonomy of the Septoria spp. associated with pistachio, and distinguishes four species associated with this host genus. Partial nucleotide sequence data for five gene loci, ITS, LSU, EF-1α, RPB2 and Btub were generated for a subset of isolates. Cylindroseptoria pistaciae, which is associated with le… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

5
24
0

Year Published

2013
2013
2021
2021

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 22 publications
(29 citation statements)
references
References 34 publications
5
24
0
Order By: Relevance
“…Notes — In resolving the Septoria/Pseudocercospora complex occurring on pistachio, Crous et al (2013c) reported that contrary to the recent circumscription of Pseudocercospora s.str. ( Crous et al 2013a ), a species with pycnidial conidiomata and pigmented conidia, Septoria pistacina (= P. pistacina ), also proved to be a member of Pseudocercospora .…”
mentioning
confidence: 96%
“…Notes — In resolving the Septoria/Pseudocercospora complex occurring on pistachio, Crous et al (2013c) reported that contrary to the recent circumscription of Pseudocercospora s.str. ( Crous et al 2013a ), a species with pycnidial conidiomata and pigmented conidia, Septoria pistacina (= P. pistacina ), also proved to be a member of Pseudocercospora .…”
mentioning
confidence: 96%
“…Hence, Alternaria spp., Aspergillus flavus, Pseudocercospora pistacina, and Septoria sp. are the main disease-causing fungal agents in the pistachio orchards of Turkey [4,5]. P. pistacina and Septoria sp.…”
Section: Introductionmentioning
confidence: 99%
“…Although pistachio is characterised by good rusticity, it is subject to several fungal diseases known to afflict pistachio trees in the Mediterranean area. Of these, the most commonly reported are phylloptosis, leaf spots mainly caused by Septoria pistaciae , S. pistaciarum and Pseudocercospora pistacina , gum cankers by Cytospora terebenthi and branch and twig cankers by Botryosphaeria dothidea ( Chitzanidis 1995 , Teviotdale et al 2002 , Vitale et al 2007 , Crous et al 2013 ). The latter is widespread and already present as a latent pathogen in numerous plant communities in various parts of the world ( Marsberg et al 2017 ).…”
Section: Introductionmentioning
confidence: 99%